MODELING AND ANALYSIS OF A SWITCHED INDUCTOR ASSISTED MODIFIED Z-SOURCE INVERTER - SUBHANI, NAFIS (2019)
Z-source inverter (ZSI) has become an attractive replacement for the voltage source inverter in the conventional dual-stage power conditioning system (PCS).